Nilai-Nilai Pendidikan Akhlak Dalam Kitab Al-Usfuriyyah Karya Syaikh Muhammad Bin Abu Bakar Al-Usfuri - Haikal Ihza Nur Muhammad; Ngarifin Shidiq; Salis Irvan Fuadi (Reflection : Islamic Education Journal, 2025)
The writing of this thesis is motivated by the many problems that occur to the younger generation that show moral degradation. This thesis aims to find out the concept of moral education values in the book Al-Usfuriyyah by Shaykh Muhammad bin Abu Bakar Al-Ushfuri and its relevance to modern Islamic education. This research uses descriptive qualitative methods with library research data collection techniques and data analysis using content analysis. The results of the study that 1) The values of moral education are an effort to form a noble person through teaching about manners, morals and ethics. 2) The content of the book of Al-Usfuriyyah covers three aspects, namely spiritual aspects (creed), moral aspects (morals), and legal aspects (sharia). 3) The values of moral education in the book of Al-Ushfuriyyah inclaud morals to Allah SWT, morals to oneself, morals to others, morals to nature. 4) The values of moral education in the book of Al-Usfuriyyah are relevant to be implemented to overcome the moral degradation that occurs, because it emphasizes the importance of fostering faith and morals as the basis for good character building.